INCREASING CALCIUM OKSIDE (CaO) TO MOULTING EXCELERATE AND SURVIVAL RATE WINDU SHRIMP (Penaeus monodon) - Indra Satrio; Mulyadi '; Iskandar ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in Apri 2016 – May 2016 for 28 days at the Hall Brackish Water Fisheries Ujung Bate, Aceh Province. The purpose of this study to determine the effect of calcium oxide (CaO) on moulting exceerate and survival rate windu shrimp (Penaeus monodon). Windu shrimp size PL25 were used in the research. The container used stoples with capacity 25 liters and the volume of water used is 20 liters. The treatment is giving of calcium oxide 45 mg/L, 60 mg/L, 75 mg/L, 90 mg/L and added the control treatment. This research uses a completely randomized design (CRD), 5 treatments and 3 replications. The results showed that the best treatment contained in P3 (75 mg/L) with the addition of calcium oxide as much the amount of shrimp molting 57 times. the absolute length of 2.82 cm, the absolute weight of 0.300 grams, daily growth rate of 6.78% and 85 % survival rate.Keywords: Calcium oxide, Penaeus monodon, moulting, survival rate